Bicentric Evaluation of Six Anti-Toxoplasma Immunoglobulin G (IgG) Automated Immunoassays and Comparison to the Toxo II IgG Western Blot - Maudry, Arnaud (American Society for Microbiology (ASM), 2009)
A comparative study of the Toxoplasma IgG(I) and IgG(II) Access (Access I and II, respectively; Beckman Coulter Inc.), AxSYM Toxo IgG (AxSYM; Abbott Diagnostics), Vidas Toxo IgG (Vidas; bioMerieux, Marcy l'Etoile, France), Immulite Toxo IgG (Immulite; Siemens Healthcare Diagnostics Inc.), and Modular Toxo IgG (Modular; Roche Diagnostics, Basel, Switzerland) tests was done with 406 consecutive serum samples. The Toxo II IgG Western blot (LDBio, Lyon, France) was used as a reference technique in the case of intertechnique discordance. Of the 406 serum samples tested, the results for 35 were discordant by the different techniques. Using the 175 serum samples with positive results, we evaluated the standardization of the titrations obtained (in IU/ml); the medians (second quartiles) obtained were 9.1 IU/ml for the AxSYM test, 21 IU/ml for the Access I test, 25.7 IU/ml for the Access II test, 32 IU/ml for the Vidas test, 34.6 IU/ml for the Immulite test, and 248 IU/ml for the Modular test. For all the immunoassays tested, the following relative sensitivity and specificity values were found: 89.7 to 100% for the Access II test, 89.7 to 99.6% for the Immulite test, 90.2 to 99.6% for the AxSYM test, 91.4 to 99.6% for the Vidas test, 94.8 to 99.6% for the Access I test, and 98.3 to 98.7% for the Modular test. Among the 406 serum samples, we did not find any false-positive values by two different tests for the same serum sample. Except for the Modular test, which prioritized sensitivity, it appears that the positive cutoff values suggested by the pharmaceutical companies are very high (either for economical or for safety reasons). This led to imperfect sensitivity, a large number of unnecessary serological follow-ups of pregnant women, and difficulty in determining the serological status of immunosuppressed individuals.